2016
DOI: 10.1002/bip.23001
|View full text |Cite
|
Sign up to set email alerts
|

DbpA is a region‐specific RNA helicase

Abstract: DbpA is a DEAD-box RNA helicase implicated in RNA structural rearrangements in the peptidyl transferase center. DbpA contains an RNA binding domain, responsible for tight binding of DbpA to hairpin 92 of 23S ribosomal RNA, and a RecA-like catalytic core responsible for double-helix unwinding. It is not known if DbpA unwinds only the RNA helices that are part of a specific RNA structure, or if DbpA unwinds any RNA helices within the catalytic core’s grasp. In other words, it is not known if DbpA is a site-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Due to this multiplicity in the interactions between the separate regions, the structural importance of the L2 linker had escaped attention. Interestingly, an elongation of the L2 linker by 23 unstructured amino acids only slightly reduced the helicase activity of DbpA ( 24 ). This can be explained by our finding that the L2 linker is only partially folded ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this multiplicity in the interactions between the separate regions, the structural importance of the L2 linker had escaped attention. Interestingly, an elongation of the L2 linker by 23 unstructured amino acids only slightly reduced the helicase activity of DbpA ( 24 ). This can be explained by our finding that the L2 linker is only partially folded ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known interaction between HP92 of the 23S rRNA and the RRM the precise role of DbpA during ribosome maturation remains unclear ( 18 , 24 ). In that light, our results provide additional insights and identify the ssRNA region preceding H90 (nt ∼2,501 to 2,508) as the binding site for the helicase core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Based on their in vitro RNA unwinding activity, many DEAD-box proteins are believed to serve as RNA chaperones. 9 12 The investigations of how the catalytic activity of DDX3X is regulated is important both for the understanding of its precise role in important cellular processes and for the design and development of potential therapeutic agents that target the DDX3X protein.…”
Section: Introductionmentioning
confidence: 99%
“…DNA‐binding protein A (dbpA)/ZO‐1‐associated nucleic acid‐binding protein is encoded by the gene Ybx3 (Frankel et al, 2005), which is a member of the cold shock protein superfamily containing a highly conserved nucleic acid‐binding motif called the cold shock domain (Li et al, 1997). The conserved cold shock domain enables dbpA to directly or indirectly bind with DNA and RNA, acting as a transcription and translation factor (Moore, Gentry, & Koculi, 2017). It has been reported that dbpA bound and inhibited the expression of cyclin‐dependent kinase 5 (Cdk5), meanwhile, dbpA protein interacts with the cyclin‐dependent kinase 4 (Cdk4) and suppressed the activity of Cdk4/cyclin D1 enzyme (Moorthamer, Zumstein‐Mecker, & Chaudhuri, 1999).…”
Section: Introductionmentioning
confidence: 99%